RNA expression profiling of nonhuman primate renal allograft rejection identifies tolerance. Issue 6 (17th February 2018) - Smith, R. N.; Matsunami, M.; Adam, B. A.; Rosales, I. A.; Oura, T.; Cosimi, A. B.; Kawai, T.; Mengel, M.; Colvin, R. B.
Abstract : Tolerance induction to prevent allograft rejection is a long‐standing clinical goal. However, convincing and dependable tolerance identification remains elusive. Hypothesizing that intragraft RNA expression is informative in both rejection and tolerance, we profile intrarenal allograft RNA expression in a mixed chimerism renal allograft model of cynomolgus monkeys and identify biologically significant tolerance. Analysis of 67 genes identified 3 dominant factors, each with a different pattern of gene expressions, relating to T cell–mediated rejection (TCMR), chronic antibody‐mediated rejection (CAMR), or Tolerance. Clustering these 3 factors created 9 groups. One of the 9 clustered groups, the Tolerance cluster, showed the lowest probability of terminal rejection, the longest duration of allograft survival, and the lowest relative risk of terminal rejection. The Tolerance factor consists of a novel set of gene expressions including cytokine and immunoregulatory genes adding mechanistic insights into tolerance. The Tolerance factor could not be identified within current pathologic diagnostic categories. The TCMR and CAMR factors are dominant to the Tolerance factor, causing rejection even if the Tolerance factor is present. These 3 factors determine the probability of terminal rejection or tolerance. This novel a posteriori approach permits identification of pathways of rejection, including tolerance. Abstract : RNA expression profiling of renal allografts identifies tolerance.